2017
DOI: 10.1021/acs.jced.6b00960
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Mineral Solubilities in the Quaternary Systems KCl–MgCl2–ZnCl2–H2O and KCl–MgCl2–PbCl2–H2O at 373 K

Abstract: In this work, the solubilities of the salt minerals in quaternary systems potassium chloride–magnesium chloride–zinc chloride–water and potassium chloride–magnesium chloride–lead chloride–water were measured at 373 K using an isothermal dissolution equilibrium method. Phase diagrams were constructed based on compositions of saturated liquid phase and existing equilibrium solid phase. By X-ray powder diffraction identification, a variety of solid forms were determined for the quaternary system KCl–MgCl2–­ZnCl2–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The NaCl−ZnCl 2 −H 2 O aqueous system has been conducted at a variety of temperatures, such as 273.15, 8 260.35, and 250.15 K. 9 Because high density fluid is used as a petroleum drilling fluid, solubilities and densities of the ternary system CaCl 2 −ZnCl 2 − H 2 O have been carried out at 273.15 and 298.15 K 10 and the system CaCl 2 +ZnCl 2 +H 2 O (NaCl saturated) was studied at T = 288.15 K. 11 The solubilities of ZnCl 2 and CO(NH 2 ) 2 in HCl have been determined at T = 298.15 K. 12 The phase equilibria of the ternary system ZnCl 2 −LiCl−H 2 O at 298 and 313 K have been conducted, 13 and it was found that the double salt 2LiCl• ZnCl 2 •2.5H 2 O was observed. In a previous study, we analyzed phase equilibria involving zinc chloride in the ternary systems KCl−ZnCl 15 To the best of our knowledge, this is the first report on phase equilibria in these two systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NaCl−ZnCl 2 −H 2 O aqueous system has been conducted at a variety of temperatures, such as 273.15, 8 260.35, and 250.15 K. 9 Because high density fluid is used as a petroleum drilling fluid, solubilities and densities of the ternary system CaCl 2 −ZnCl 2 − H 2 O have been carried out at 273.15 and 298.15 K 10 and the system CaCl 2 +ZnCl 2 +H 2 O (NaCl saturated) was studied at T = 288.15 K. 11 The solubilities of ZnCl 2 and CO(NH 2 ) 2 in HCl have been determined at T = 298.15 K. 12 The phase equilibria of the ternary system ZnCl 2 −LiCl−H 2 O at 298 and 313 K have been conducted, 13 and it was found that the double salt 2LiCl• ZnCl 2 •2.5H 2 O was observed. In a previous study, we analyzed phase equilibria involving zinc chloride in the ternary systems KCl−ZnCl 15 To the best of our knowledge, this is the first report on phase equilibria in these two systems.…”
Section: Introductionmentioning
confidence: 99%
“…The phase equilibria of the ternary system ZnCl 2 –LiCl–H 2 O at 298 and 313 K have been conducted, and it was found that the double salt 2LiCl·ZnCl 2 ·2.5H 2 O was observed. In a previous study, we analyzed phase equilibria involving zinc chloride in the ternary systems KCl–ZnCl 2 –H 2 O and CaCl 2 –ZnCl 2 –H 2 O and quaternary system KCl–MgCl 2 –ZnCl 2 –H 2 O . Furthermore, we determined water salt systems involving lead chloride at 373 K, including ternary systems CaCl 2 –PbCl 2 –H 2 O and PbCl 2 –ZnCl 2 –H 2 O and quaternary system KCl–MgCl 2 –PbCl 2 –H 2 O .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation